2015
DOI: 10.17306/j.afs.2015.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Eff ects of natural antioxidants on colour stability, lipid oxidation and metmyoglobin reducing activity in raw beef patties

Abstract: Background. Minced meats undergo oxidative changes and develop rancidity more quickly than intact muscle since grinding exposes more of the muscle surface to air and microbial contamination. Due to concerns about toxicological safety of synthetic antioxidants, recent studies have put more focus on natural antioxidant compounds derived from food components. Material and methods. The effects of four natural antioxidants (vitamin E, carnosine, grape seed extract and tea catechins) on oxidative processes and metmy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 27 publications
13
28
0
Order By: Relevance
“…The increase in TBARS over storage coincides with the decrease in the concentration of tocopherols and total carotenoids. The increase in TBARS value is consistent with previous findings in which the TBARS values of refrigerated broiler meat 2012a;Olorunsanya et al, 2011), goat meat (Karami et al, 2011;Sabow et al, 2015a) and beef (Popova et al, 2009;Liu et al, 2015) increased as storage progressed.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The increase in TBARS over storage coincides with the decrease in the concentration of tocopherols and total carotenoids. The increase in TBARS value is consistent with previous findings in which the TBARS values of refrigerated broiler meat 2012a;Olorunsanya et al, 2011), goat meat (Karami et al, 2011;Sabow et al, 2015a) and beef (Popova et al, 2009;Liu et al, 2015) increased as storage progressed.…”
Section: Resultssupporting
confidence: 91%
“…The decrease in redness as post mortem storage progressed could be because of the oxidation of myoglobin (deoxymyoglobin or oxymyoglobin) to form metmyoglobin owing to decreased metmyoglobin reducing activity (MRA). The increase in MetMb concentration over storage is in tandem with the findings of Liu et al (2015), who observed an increase in the MetMb concentration of beef patties aged for 8 d. The decrease (P< 0.05) in MRA over storage is consistent with the findings of Madhavi & Carpenter (1993), who observed a reduction in MRA of beef aged for 21 d. Contrarily, a significant increase in the MRA of beef patties over an 8-d post mortem storage was observed (Liu et al, 2015). The inconsistencies among studies over the effect of post mortem ageing on MRA of meat could be because of differences in the methodology, the rate of myoglobin oxidation, and the efficacy of one or more enzymes required to reduce the formed metmyoglobin (Bekhit & Faustman, 2005).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Several findings observed that the fresh meat packaged with antioxidant film could inhibit metmyoglobin formation throughout the storage (Gallego et al, 2016;Lorenzo, Batlle, & Gómez, 2014;Nerín, Tovar, & Salafranca, 2008;Xu et al, 2010). Similar trends were demonstrated by Liu, Xu, Dai, and Ni (2015) where the direct incorporation of vitamin E in raw beef patties delayed the formation of metmyoglobin during storage.…”
Section: Metmyoglobin In Meat Pattiessupporting
confidence: 58%
“…In this regard, Mitsumoto et al . and Liu et al . also concluded that tea catechins at concentrations close to 300 ppm were capable of effectively retarding lipid oxidation.…”
Section: Discussionmentioning
confidence: 98%